2019
DOI: 10.1080/1354750x.2019.1609579
|View full text |Cite
|
Sign up to set email alerts
|

Effects of reduced exposure to cigarette smoking on changes in biomarkers of potential harm in adult smokers: results of combined analysis of two clinical studies

Abstract: Purpose: Nonconventional vapor products (NVP), designed to reduce exposure to cigarette smoke toxicants (CSTs), could cause changes in biomarkers of potential harm (BoPH). Although, NVPs reduced CSTs exposure compared to conventional cigarettes (CC), the changes in the BoPH values varied among the studies. Hence, further information on BoPH using NVPs is needed. Material and methods: The data of two similarly designed studies using a kind of NVP, a noncombustion and nonheating inhaler type of smokeless tobacco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Even though urinary and plasma MDA concentrations are associ-ated, and plasma MDA concentrations have been shown to be different in smokers and non-smokers [73,74], we did not find a clear difference in smoking status, albeit the median urinary MDA concentration values seemed slightly higher among smokers. Other studies [34,75] have shown urinary MDA concentrations to be significantly greater in smokers compared to non-smokers. The lack of observed difference between these groups in our review might be related to the number of cigarettes smoked, as suggested in a previous review [74], which found a dose-dependent relationship between cigarette smoke exposure and plasma MDA concentration.…”
Section: Heterogeneity In Data Collection Of Demographicsmentioning
confidence: 86%
See 1 more Smart Citation
“…Even though urinary and plasma MDA concentrations are associ-ated, and plasma MDA concentrations have been shown to be different in smokers and non-smokers [73,74], we did not find a clear difference in smoking status, albeit the median urinary MDA concentration values seemed slightly higher among smokers. Other studies [34,75] have shown urinary MDA concentrations to be significantly greater in smokers compared to non-smokers. The lack of observed difference between these groups in our review might be related to the number of cigarettes smoked, as suggested in a previous review [74], which found a dose-dependent relationship between cigarette smoke exposure and plasma MDA concentration.…”
Section: Heterogeneity In Data Collection Of Demographicsmentioning
confidence: 86%
“…Figure 5. Forest plot of urinary MDA concentration (mg/g creatinine) in healthy adult (18+ years) by smoking/non-smoking groups (non-smok:[31][32][33][34][35]37,39,40,42,43,45,50,51,56,62], mixed:[38,45,50,54,59,60], smokers:[34,37,39,42,62], NA:[7,30,36,41,44,[46][47][48][49]52,53,55,57,58,61,63].…”
mentioning
confidence: 99%
“… 33 There is a trend for levels of 11-DHTXB2, 2,3-d-TXB2, and 8-epi-PGF2α to be higher in smokers than in non-smokers in healthy subjects. 20 , 44 , 45 , 50 Elevated levels of 11-DHTXB2, 2,3-d-TXB2, and 8-epi-PGF2α in smokers were reported to decrease following smoking cessation. 4 , 20 In the present study, significantly lower levels of 11-DHTXB2, 2,3-d-TXB2, and 8-epi-PGF2α in NTV users compared to CC smokers were found and there was no difference between the NTV users and the NS subjects in biomarker levels except for 2,3-d-TXB2 (2,3-d-TXB2: NTV > NS, p = .0312).…”
Section: Discussionmentioning
confidence: 99%